Exploring Customer Loyalty through User Experience and Customer Satisfaction on Kopi Kenangan Mobile App - adawiyah; aditya putra; siti nurfitriana (LIAISON JOURNAL OF BEST, 2023)
The development of the mobile application has reached the food and beverages sector.The presence of a food and beverage mobile application can ease our lives to order our food and drinks from anywhere. By that, user experience has become one of the factors of customer satisfaction and led to customer loyalty. This research focuses on exploring customer loyalty through user experience and customer satisfaction on Kopi Kenangan mobile app. Kopi Kenangan is one of the fastest-growing new retail food and beverage business that use mobile application for convenience of their users to buy their products. This research usesa descriptive and quantitative approach with conducts to find the relationship between three variables, namely user experience, customer satisfaction, and customer loyalty with their respective variables. This research uses quantitative data as data collection methods in the form of questionnaires with the population whocame from Kopi Kenangan mobile application user who has been using Kopi Kenangan mobile application to buy Kopi Kenangan products. The purpose of this research is to analyze the positivesignificance of user experience and customer satisfaction to customer loyalty. This research shows both user experience and customer satisfaction shows positive significance to customer loyalty.Keywords: Kopi Kenangan mobile app, User Experience, Customer Satisfaction, Customer loyalty